2021
DOI: 10.1038/s41598-021-96690-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acanthamoeba genotypes from public freshwater sources in Thailand reveals a new genotype, T23 Acanthamoeba bangkokensis sp. nov.

Abstract: A survey of Acanthamoeba in 100 public freshwater sources in 28 provinces across Thailand has identified 9 genotypes comprising T2/6, T3-T5, T9, T11, T12, T18 and a novel ‘T23’ among 131 isolates. Sequencing of the near complete 18S rRNA gene of Acanthamoeba of all isolates has shown that the most predominant genotype T4 found in 87 isolates (66.4%) contained 4 subtypes, i.e. T4A, T4B, T4C and T4F, while all isolates assigned to genotype T2/6 belonged to subtype B. Among intron-bearing genotypes, most isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 61 publications
(84 reference statements)
1
31
0
Order By: Relevance
“…However, we had a small dataset and further studies with large sample sizes are warranted. Determining the genotype of represented species was limited by the quantity of the specimen available; however, A. castellanii has been shown to correspond to genotypes T1 or T4, and A. polyphaga to T2 or T4 [13] (see Table 7). It has been previously shown that the T4 genotype is the most pathogenic [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, we had a small dataset and further studies with large sample sizes are warranted. Determining the genotype of represented species was limited by the quantity of the specimen available; however, A. castellanii has been shown to correspond to genotypes T1 or T4, and A. polyphaga to T2 or T4 [13] (see Table 7). It has been previously shown that the T4 genotype is the most pathogenic [21].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the number of cases in non-contact lens wearers in Asian countries has grown in recent years ( 2 , 3 ). Based on previous studies, Acanthamoeba species are distributed into 23 different ribogenotypes (T1–T23) ( 4 6 ). Although genotypes of T4 are the most prevalent, AK caused by non-T4 genotypes is associated with more severe outcomes ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on rRNA gene sequence analyses, 23 different genotypes have been reported to date (T1 to T23), with T4 being the most abundant genotype in both clinical and environmental samples. Acanthamoeba are mixotrophic and can encyst under unfavorable conditions [ 2 , 3 ]. Currently, the treatment of Acanthamoeba infections remains an issue, due to the presence of cyst forms and to the variability in drug efficacy among different genotypes, in addition to the long periods of drug administration and drug toxicity.…”
Section: Introductionmentioning
confidence: 99%